Study of the ionic liquidsâ electrochemical reduction using experimental and computational methods - Abdalmageed Saadaldeen Mohammed, S. (Elsevier B.V., 2022)
Ionic liquids (ILs) as electrolytes have attracted attention because of their distinctive properties. Numerous studies on the electrochemical stability of the ILs have been published. However, a deep understanding of the parameters that affect the reduction stability is highly required. In this study, the reduction potentials of five ILs including two novel ILs that contain 1,2,4-triazolium as cation were evaluated experimentally using cyclic voltammetry (CV) and compared with computational modeling using Tmolex software and Conductor like Screening Model for Real Solvents (COSMO-RS). We investigate the parameters that affect the ILsâ reduction stability such as the lowest unoccupied molecular orbital (LUMO) energy levels of the cations and anions, as well as the effect of the molecular interaction between them. We conclude that while using the computational method, the individual values of the LUMO of the cations or anions without taking into consideration the molecular interaction might misguide the prediction of the ILs reduction stability. Â© 2022 Elsevier B.V.